2013
DOI: 10.1371/journal.pone.0057705
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of a Pine Plantation Receiving Repeated Applications of Biosolids

Abstract: Treated biosolids have been applied to 750-ha of a Pinus radiata forest plantation on Rabbit Island near Nelson City in New Zealand since 1996. A long-term research trial was established in 1997 to investigate the effects of the biosolids applications on the receiving environment and tree growth. An analysis of the likely economic impact of biosolids application shows that biosolids application has been beneficial. Stem volume of the high treatment (biosolids applied at 600 kg N ha-1 every three years) was 36%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The likely profit obtained by the lower cost of fertilizers and shorter rotations can offset the costs of transportation and sludge application in Eucalyptus plantations as, for example, was found in pine (Wang et al, 2013) and poplar (Ramlal et al, 2009) plantations treated with sludge. Additionally, the reuse of sewage sludge could provide a low-cost alternative for its expensive and complex disposal and management (Guerrini et al, 2017) with, consequently, the possibility of turning currently bulky refuse material into a commodity (Capra et al, 2013).…”
Section: Recommendations For Using Sewage Sludge Together With Mineramentioning
confidence: 99%
See 1 more Smart Citation
“…The likely profit obtained by the lower cost of fertilizers and shorter rotations can offset the costs of transportation and sludge application in Eucalyptus plantations as, for example, was found in pine (Wang et al, 2013) and poplar (Ramlal et al, 2009) plantations treated with sludge. Additionally, the reuse of sewage sludge could provide a low-cost alternative for its expensive and complex disposal and management (Guerrini et al, 2017) with, consequently, the possibility of turning currently bulky refuse material into a commodity (Capra et al, 2013).…”
Section: Recommendations For Using Sewage Sludge Together With Mineramentioning
confidence: 99%
“…One of the most promising benefits in using sewage sludge in Eucalyptus plantations is the enhancement of net primary production. Previous studies have reported early growth increase in pine tree plantations with the use of sludge (Kimberley et al, 2004;Wang et al, 2013). Further gain is expected by using sludge coupled with a complementary dose of mineral N and P fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Some 60% of these biosolids are landfilled, 10% are discharged in oceans, and only 30% are applied to land (ANZBP, 2016), despite the NZ waste strategy that states that 95% of biosolids should be beneficially reused (Bradley, 2008). Historically, biosolids have been applied to pine plantations, where they accelerate growth at the expense of wood quality (Wang et al, 2004, 2013; Xue et al, 2015).…”
mentioning
confidence: 99%
“…Application of biosolids onto forest land is often preferred to on agricultural land because the biosolids can increase tree growth and subsequent economic returns Prescott and Blevins, 2005;Wang et al, 2013) without the risk of contaminants entering the human food chain (Magesan and Wang, 2003). Many studies have investigated responses of forest growth (Harrison et al, 2001;Lteif et al, 2007;Scharenbroch et al, 2013), tree nutrition (Feldkirchner et al, 2003;Wang et al, 2004), soil properties (Kowaljow et al, 2010;Luo and Christie, 2001;Wang et al, 2003) and ecosystems (Banaitis et al, 2009;Wang et al, 2005) to short-term (1-5 years) application of biosolids.…”
Section: Introductionmentioning
confidence: 99%